Elucidating the reaction mechanism of SnF2@C nanocomposite as a high-capacity anode material for Na-ion batteries. (December 2017) - Ali, Ghulam; Lee, Ji-Hoon; Oh, Si Hyoung; Jung, Hun-Gi; Chung, Kyung Yoon
Abstract: Sn-based materials have drawn great attention as anodes for rechargeable batteries because of their extremely high theoretical energy storage capacities. Herein, a nanocomposite based on SnF2 and acetylene black is proposed as a high-performance anode material for sodium-ion batteries and their electrochemical performances, as well as related energy storage mechanism, are investigated. The nanocomposite electrode delivered a high reversible capacity of 563 mAh g −1 which is considerably improved compared to a reversible capacity of 323 mAh g −1 of the micron-sized bare SnF2 electrode. The nanocomposite electrode shows superior rate capability and delivers a reversible capacity of 191 mAh g −1 at a high current density of 1 C, while the bare electrode delivers negligible capacities. The changes in crystallographic structure are observed using in-situ XRD and the results reveal the existence of a solid solution of two or more species during dis/charging. The electronic and atomic configurations depending on the state of dis/charging are systematically investigated using ex-situ X-ray absorption spectroscopy. The results reveal that the valence change of Sn follows the conversion (SnF2 + 2Na → Sn + 2NaF) and alloying (Sn + XNa → SnNaX ) reaction upon sodium insertion into a composite. Graphical abstract: Highlights: A nanocomposite of SnF2 and acetylene black is prepared using ball-milling method. The nanocomposite delivers exceptional electrochemical properties. GITT results indicate higher values of DNa in the nanocomposite. In-situ XRD results suggest a solid solution during sodiation process. The reaction mechanism involves conversion and alloying reaction.